REGULATION AND ETHICS IN THE UTILIZATION OF ARTIFICIAL INTELLIGENCE IN RELIGIOUS-MODERATION DA’WAH: A LITERATURE STUDY ON THE INTEGRATION OF TRADITIONAL AND DIGITAL IJTIHAD - Irfan Ahmad Harfan (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2026)
The digitalization of Islamic preaching in Indonesia is now marked by religious chatbots, digital exegesis systems, and content-recommendation engines, yet these machines possess neither scholarly chain of transmission (sanad) nor moral consciousness, making interpretive authority an urgent concern for the religious-moderation agenda. This study identifies models of artificial intelligence use in religious-moderation da’wah, analyzes their epistemological and ethical challenges, and formulates a regulatory framework integrating traditional and digital ijtihad. Employing a library-research method on twelve primary sources, comprising journal articles from 2020–2025, Ministry of Religious Affairs documents, and statements from the Indonesian Ulema Council and Nahdlatul Ulama, analyzed through the Miles and Huberman interactive model, the study finds three dominant models of artificial-intelligence-assisted da’wah, identifies the absence of sanad and moral awareness in machines as the principal epistemological challenge, and proposes a supervised digital-ijtihad framework synergizing ulema, government, and technology developers under the principles of maqashid al-shariah.